Evaluation of serum Ferritin level in patients presenting with dysphagia: A hidden marker to diagnose Plummer Vinson syndrome - Rukhsana Tumrani; Afshan Qayum; Kashif Munir; Ahmad Ijlal; Mehvish Sana (Journal of Rawalpindi Medical College)
Objective: 1) To evaluate the serum ferritin level in patients presenting with dysphagia. 2) To determine the frequency of low serum ferritin in Plummer Vinson syndrome